Association of glutathione S-transferase M1 and T1 genotypes with asthma: A meta-analysis. Issue 34 (21st August 2020) - Su, Xinming; Ren, Yuan; Li, Menglu; Kong, Lingfei; Kang, Jian
Abstract: Background: We performed an updated meta-analysis to clarify the relationship between glutathione S -transferase Mu and theta (GSTM1 and GSTT1, respectively) null/positive genotypes and asthma. Methods: We performed a literature search using PubMed and Web of Science databases in August 2019. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the role of GSTM1 and GSTT1 genotypes in the risk of asthma. Results: Overall, we found a significant association with asthma risk in the general population for both the GSTM1 genotype (OR = 1.21; 95% CI: 1.07–1.35; P < .001; I 2 = 69.5%) and the GSTT1 genotype (OR = 1.61; 95% CI: 1.30–2.00; P < .001; I 2 = 83.6%). Moreover, significant associations between both genotypes and asthma risk were also found by age stratification. Furthermore, for GSTM1 we found significant associations in populations living in Asia, Europe, and Russia, but not in Africa. Conversely, for GSTT1, we found a significantly increased risk in populations living in Asia, Europe, Africa, and Russia. In addition, a significant association was found for both genotypes with a sample size <500, but not a sample size >2000. Conclusion: Our meta-analysis provides evidence that GSTM1 and GSTT1 genotypes could be used as asthma-associated biomarkers.